2010
DOI: 10.1016/j.virol.2010.08.030
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ production downstream of NKT cell activation in mice infected with influenza virus enhances the cytolytic activities of both NK cells and viral antigen-specific CD8+ T cells

Abstract: Natural killer T (NKT) cell activation is responsible for eliminating pathogens. However, the biological functions of NKT cells against influenza virus are not fully understood. We therefore investigated the effects of NKT cells in viral infection using CD1d knockout (KO) mice. When CD1d KO or wild-type (WT) mice were infected with a sub-lethal dosage of the influenza virus, the survival rate of CD1d KO mice was significantly lower than for WT mice in association with delayed viral clearance in the lungs. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
6
42
1
Order By: Relevance
“…Thus, iNKT cell deficiency accelerates lung injury and the fatal outcome in our system. This finding is in agreement with other studies reporting beneficial effects of NKT cells, including iNKT cells, during acute respiratory viral infection (20,34,35) and suggests that iNKT cells play a part in the control of airway inflammation and susceptibility to IAV (H3N2)-associated mortality. The exact mechanisms by which iNKT cells attenuate IAV pathogenesis are yet to be defined.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, iNKT cell deficiency accelerates lung injury and the fatal outcome in our system. This finding is in agreement with other studies reporting beneficial effects of NKT cells, including iNKT cells, during acute respiratory viral infection (20,34,35) and suggests that iNKT cells play a part in the control of airway inflammation and susceptibility to IAV (H3N2)-associated mortality. The exact mechanisms by which iNKT cells attenuate IAV pathogenesis are yet to be defined.…”
Section: Discussionsupporting
confidence: 93%
“…Our initial observation that both immature and mature CD1d KO mice were more susceptible to intra-vaginal HSV-2 infection than WT mice is supported by Ashkar and Rosenthal (2003), who found CD1d KO mice to be 10-fold more susceptible to vaginal HSV-2 infection than WT mice. Similar findings have been made for HSV-1, influenza virus and encephalomyocarditis virus infections (GruborBauk et al, 2003;Ishikawa et al, 2010;Exley et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, NKT cells have cytolytic activities owing to expression of granzyme B, perforin, and FasL (Wu et al, 2009). There is increasing evidence that NKT cell-dependent activation of NK cells play a central role in the protective mechanisms (Ishikawa et al, 2010;Exley et al, 2003). This is supported by the finding that specific activation of NKT cells leads to activation of NK cells and that this response is lost in CD1d KO mice (Carnaud et al, 1999;Eberl and MacDonald, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Two previous murine studies showed that α-GalCer administered by intraperitoneal (i.p.) injection increased survival in mice infected with a lethal dose of the IAV A/PR8/342122. A third study found that weight profile and viral titers improved in mice infected with a non-lethal dose of the human IAV E61-13-H17 when α-GalCer was administered i.p., but not through the intranasal route23.…”
Section: Discussionmentioning
confidence: 96%